TMEM16F phospholipid scramblase regulates tumorigenesis by modulating the tumor immune microenvironment - Menghan Wu; Peishang Shi; Jianmin Huang; Xiaomin Ni; Ruijia Lai; Kun Cao; Mengya Cai; Hao Yu; Wenshan Zhao; Yang Zhang (Proceedings of the National Academy of Sciences, 2025)
The immunosuppressive tumor microenvironment enables immune evasion through mechanisms beyond canonical immune checkpoints. While phosphatidylserine (PS) externalization coordinates apoptotic clearance under physiological conditions, tumors hijack this mechanism through apoptotic mimicry to subvert antitumor immunity. Here, we identify TMEM16F, a calcium-activated phospholipid scramblase, as a driver of tumor-intrinsic PS externalization. TMEM16F-mediated PS scrambling polarized macrophages to an immunosuppressive M2 phenotype, which promotes TGF-β1 secretion and regulatory T cell expansion to suppress cytotoxic lymphocytes. Genetic ablation of TMEM16F abolished PS exposure, systemically reprogrammed the tumor microenvironment and primary immune organs toward immune activation, and suppressed tumor growth across cancer models. Pharmacological scramblase inhibition produced these effects, demonstrating therapeutic potential. Our findings establish TMEM16F-dependent phospholipid scrambling as a critical immune evasion axis and propose targeting this pathway for cancer treatment.